2022
DOI: 10.1186/s10194-022-01483-z
|View full text |Cite
|
Sign up to set email alerts
|

Serum CGRP in migraine patients using erenumab as preventive treatment

Abstract: Aim Serum levels of Calcitonin Gene-Related Peptide (CGRP)-like immunoreactivity (CGRP-LI) in migraine patients before and after starting treatment with erenumab were measured to evaluate the association with clinical treatment response. Methods Blood samples were collected from the cubital fossa before (T0) and 2–4 weeks after (T1) starting treatment with erenumab. Clinical response was monitored using a daily headache e-diary. Serum levels of CGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
3
8
0
Order By: Relevance
“…In our larger cohort of patients treated with erenumab, free CGRP plasma levels did not differ from those of prophylaxis-naïve patients and remained stable after treatment discontinuation. In line with our results, a recent study on serum CGRP concentrations did not show any difference between before and 2–4 weeks after starting erenumab treatment [ 14 ]. Similarly, a study on salivary CGRP levels detected no significant change during 12 weeks of erenumab therapy [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our larger cohort of patients treated with erenumab, free CGRP plasma levels did not differ from those of prophylaxis-naïve patients and remained stable after treatment discontinuation. In line with our results, a recent study on serum CGRP concentrations did not show any difference between before and 2–4 weeks after starting erenumab treatment [ 14 ]. Similarly, a study on salivary CGRP levels detected no significant change during 12 weeks of erenumab therapy [ 19 ].…”
Section: Discussionsupporting
confidence: 93%
“…CGRP-targeted treatments in particular are thought to have an impact on CGRP plasma concentrations [ 12 ]. However, a proof-of-concept and a second study on CGRP in peripheral blood in patients on erenumab remained inconclusive [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our novel objective was to describe how the serum levels of CGRP evolve throughout the course of anti‐CGRP/CGRP‐R mAb treatments. A very recently published study has found erenumab numerically decreases the baseline serum CGRP levels at 2 to 4 weeks since the first dose, although the differences were not significant 32 . Here, our results show that these therapies have a lowering effect on the circulating concentrations of alpha‐CGRP not only at 2 weeks since its initiation but also at 3 months since the first dose, identical for both antibodies against the ligand and its receptor.…”
Section: Discussionsupporting
confidence: 58%
“…A very recently published study has found erenumab numerically decreases the baseline serum CGRP levels at 2 to 4 weeks since the first dose, although the differences were not significant. 32 Here, our results show that these therapies have a lowering effect on the circulating concentrations of alpha-CGRP not only at 2 weeks since its initiation but also at 3 months since the first dose, identical for both antibodies against the ligand and its receptor. On top of that, there was a correlation between the amount of circulating alpha-CGRP decreased by the therapies within the first 3 months and the reduction of MMD at the third month of treatment.…”
Section: Discussionsupporting
confidence: 56%
“…A few studies have investigated the prediction of treatment efficacy to mAbs against CGRP signaling using blood-based measurements of CGRP [ 7 , 46 ]. In a recent study of 94 patients with migraine treated with erenumab, baseline serum CGRP levels were not found to predict treatment response, but the treatment period was only 2–4 weeks [ 10 ]. Another recent study found that 96 patients with chronic migraine showed elevated levels of serum CGRP compared to healthy controls, and that these levels subsequently normalized at two weeks and at three months during treatment with erenumab [ 11 ].…”
Section: Discussionmentioning
confidence: 99%